Strengthening Accounting Information Quality on SME Community Based on Artificial Intelligence and Integrated Reporting Stakeholder Trust - Muhammad Hafis Akbar Nasution; Andreasta Ginting; Emi Uliyanty Br Sidabutar; Jenny Ester Pandiangan (Golden Ratio of Data in Summary, 2026)
This study aims to examine how artificial intelligence readiness and integrated reporting contribute to accounting information quality and, in turn, influence investor trust and corporate performance in a sustainability-oriented business context. Employing a qualitative research approach grounded in a comprehensive literature review, this study systematically reviews and synthesizes recent and seminal academic work in accounting, corporate reporting, artificial intelligence, and capital markets. The method involves thematic and content analysis of peer-reviewed journal articles and authoritative institutional reports to identify recurring patterns, theoretical linkages, and convergent findings related to the proposed constructs. The results indicate that artificial intelligence readiness and integrated reporting function as complementary organizational capabilities that enhance accounting information quality by improving accuracy, transparency, and contextual coherence of corporate disclosures. Accounting information quality emerges as a key mediating mechanism through which technological readiness and reporting architecture strengthen investor trust. The findings further suggest that higher investor trust facilitates improved corporate performance by reducing information asymmetry, lowering the cost of capital, and supporting long-term sustainable value creation. The main contribution of this study lies in developing an integrated conceptual understanding that connects digital readiness, advanced reporting practices, and sustainability-oriented performance outcomes. This study provides theoretical insights for accounting and disclosure research. It offers practical implications for managers seeking to align digital transformation and reporting strategies with investor expectations and sustainable corporate performance.